Preliminary results of metamorphic P-T studies on East Sør-Rondane, Antarctica - Grantham, G.H.; Kawakami, T.; Ishikawa, M; Satish-Kumar, M; Tsuchiya, N; Graser, P. (2010)
第30回極域地学シンポジウム「極域から探る固体地球ダイナミクス」 ポスター発表 conference object